PENGARUH KADAR HEMOGLOBIN DAN HEMATOKRIT TERHADAP EKLAMSIA PADA IBU HAMIL DENGAN PRE EKLAMSIA BERAT DI RSUD MARGONO SOEKADJO PURWOKERTO TAHUN 2013 - ., Sumarni; Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Hemoconcentration is a major sign of pre-eclampsia. Normal blood volume increases during pregnancy occurs almost entirely in women pre-eclampsia. Hemoglobin levels in pre-eclamptic women did not differ significantly between groups of pre-eclampsia and severe pre-eclampsia light. Knowing the influence of Hemoglonin and Hemotocrit against Eclampsia in pregnant women with pre-eclampsia in hospitals Tanuwijaya Soekardjo Navan in 2013. This research is analytic survey with cross sectional design. The sample in this study were pregnant women who developed pre-eclampsia eklamsai weight and that in reference to RS Margono Soekardjo as many as 66 people. The data analysis using pair T test. HB and HT levels on average in pregnant women who developed pre-eclampsia and eclampsia is 11.95 g%, the maximum value of HB 17 g%, 6.55 mg / dl, HT maximum value is 50 mg / dl, No influence of significance between HB and HT in pregnant women with pre-eclampsia in pregnant women with eclampsia with the value (p = 0.091; p = 0.299). Kata Kunci : HB, HT, Pre eklamsia, Eklamsia